MODELING TECHNICAL, ECONOMIC AND ENVIRONMENTAL PARAMETERS OF FOREST MACHINES ACCORDING TO THE VOLUME OF THE TREES - Ferreira do Nascimento Santos, Diego Weslly; Magalhães Valente, Domingos Sarvio; Fernandes, Haroldo Carlos; Ribeiro Furtado Júnior, Marconi; Nunes dos Santos, Larissa (Floresta, 2022)
Increasing harvester and forwarder productivity and maintaining fuel consumption is the key to more efficient forest harvesting, with less environmental impact and greater economic returns. Therefore, the objective of this research was to evaluate the influence of the volume of trees on technical, economic, and environmental parameters of harvester and forwarder in eucalyptus forests. The research was carried out in the municipality of Teixeira de Freitas, Bahia, Brazil. Were evaluated the harvester and forwarder operations in forest stands with an average individual tree volume of 0.08; 0.12; 0.16 and 0.20 m³ tree-1. Productivity, energy demand, production cost and amount of carbon dioxide emitted were determined. The data were submitted to regression analysis, and the models were adjusted utilizing the determination coefficient, phenomenon behavior, and significance of the regression coefficients. To obtain a forest harvest with less environmental impact and more economically viable, trees should be felled with an individual average volume between 0.16 and 0.20 m³ tree-1.